NiO/MWCNTs Coated F-doped Tin Oxide Working Electrode for Hydrogen Peroxide Detection - Boonsong Jandai; Papitchaya Woointranont; Suwan Chaiyasith; Wisanu Pecharapa (My University, 2011)
In this work, NiO/MWCNTs composites were synthesized by heat treatment via two methods. MWCNTs was treated by classical oxidative with acid. The treated MWCNTs was mixed with Nickel acetate in various concentration before calcined at 400 °C for 2 h to obtain the NiO/MWCNTs and compared with another method that prepared by chemically depositing nickel hydroxide onto carbon nanotubes under microwave irradiation and thermal annealing process. The modified electrode for the detection of hydrogen peroxide was successfully developed on cross-linking between NiO/MWCNTs nanocomposites and fluorine-doped tin oxide (FTO) using nafion as binder. The physical properties of the composites were investigated by Field Emission Scanning Electron Microscope (FE-SEM) and X-ray Diffractometer (XRD). The SEM results indicated that NiO nanoparticles were well distributed on the surface of MWCNTs. The cyclic voltammetry were used to confirm the successful procedure synthesis of NiO/MWCNTs/FTO and the concentration of hydrogen peroxide was determined by amperometry, by mean of the NiO/MWCNTs/nafion/FTO as working electrode.
Keywords: Non-blocking I/O; Nickel oxide; Tin oxide; Amperometry; Conducting polymers and applications